Energy consumption intensity in Sub-Saharan Africa: Evidence and policies - Aboagye, S.; Nketiah-Amponsah, E. (University of Ghana, 2015)
The aftermath of the 1970 oil price shock coupled with rapid urbanization, rising population, industrialization and increased environmental degradation in Sub Saharan Africa (SSA), have necessitated a shift of emphasis from energy consumption to a thorough investigation into energy consumption intensity. This notwithstanding, the evidence remains sparse for SSA as literature has not adequately examined the effects of SSA's economic growth process on energy intensity in the region and this is what the study addresses using a panel dataset from 1980-2010 covering 36 SSA countries. A system Generalized Method of Moment (GMM) estimation confirmed the existence of a U-shaped economic growth-energy consumption intensity nexus in SSA. Additionally, both urbanization and industrialization are found to increase energy consumption intensity while the contrary existed for FDI and trade. Inflation was not found to include the drivers of energy consumption intensity. Against these we discuss some policy options.
School of social sciences colloquium
Keywords: Sub Saharan Africa (SSA); energy consumption; Generalized Method of Moment (GMM); urbanization; Inflation